A simplified strategy for the estimation of the exercise ventilatory thresholds - Neder, J. A.; Stein, R. (Medicine & Science in Sports & Exercise, 2006)
Purpose: To analyze the limits of agreement between exercise ventilatory threshold values (VT1 and VT2) estimated from a combination of pulmonary gas exchange and ventilatory variables (cardiopulmonary exercise testing) and those derived from an alternative approach based on the ventilatory response only ([latin capital V with dot above]E, ventilometry).